2004
DOI: 10.7205/milmed.169.7.522
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Residency on Physical Fitness among Military Physicians

Abstract: Physical fitness declines during medical residency training. This effect is most notable in residents with higher levels of fitness at the start of medical education. Further studies are necessary to evaluate for a similar decline among civilian residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Interestingly, the same study found that residents who reported less physical activity were more likely to report burnout. 5 Another study 6 followed military physicians throughout their residency training, and found a decline in all training activities, including push-ups, sit-ups, and 2-mile run times as residency progressed. The overall findings have demonstrated that a decrease in physical activity among residents has led to decrease iṅ VO 2 max (and thus increased fitness age as an indicator of declining cardiorespiratory fitness), which can predict long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same study found that residents who reported less physical activity were more likely to report burnout. 5 Another study 6 followed military physicians throughout their residency training, and found a decline in all training activities, including push-ups, sit-ups, and 2-mile run times as residency progressed. The overall findings have demonstrated that a decrease in physical activity among residents has led to decrease iṅ VO 2 max (and thus increased fitness age as an indicator of declining cardiorespiratory fitness), which can predict long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[30] However, residents are less likely to exercise regularly than medical students or attendings, [21], [31] and a survey of radiology residents found that only 37% engaged in recommended guidelines for physical activity. [20] A study of military physicians found that physical fitness declined and weight increased during residency training, [32] and a study of 375 residents from two academic medical centers found that third year medical residents were more likely to be overweight than first year residents [33].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies published on the fitness of medical residents are discouraging. Suskin and colleagues 11 found that a group of 20 residents experienced decreased aerobic fitness throughout rotations, and Arora and colleagues 12 reported similar results in military physicians. In a recent survey, internal medicine residents reported a significant decrease in physical activity once they began residency and noted time constraints as the primary barrier.…”
mentioning
confidence: 82%